PENGARUH VARIASI INTERSLICE GAP TERHADAP KUALITAS CITRA DAN INFORMASI CITRA ANATOMI PADA MRI BRAIN POTONGAN AXIAL T1WI SPIN ECHO - M. Ainul Mala; Luthfi Rusyadi; Sudiyono (Perhimpunan Radiografer Indonesia (PARI), 2019)
Background : Interslice gap is the distance between slices, usually its value is based on the percentage of slice thickness, interslice gap is one of the parameters that can affect the quality of MRI image. Rarely are radiographers willing and able to manipulate the value of the interslice gap, so it can produce a good image. The purpose of this study is, to determine the effect of interslice gap variation on quality on MRI brain pieces axial T1WI spin echo, to know the difference of interslice gap variation to anatomical image information on MRI brain T1WI spin echo axial, to know the value of interslice gap which has an optimal anatomical image information on MRI brain T1WI spin echo axial. Methods : This type of research is quantitative and qualitative with an experimental approach. The research was conducted at the General Hospital of dr. Sardjito Yogyakarta. The data were 32 images of MRI brain T1WI spin echo from the variation of interslice gap used 0%, 10%, 20%, and 30% from slice thickness 5 mm. The test was performed on image quality that was statistically analyzed by linear regression test. While for information of anatomical image analyzed with Friedman test, from friedman test can be known information of best anatomical image, seen from mean rank. Results : The results of this study indicate that there is an effect of interslice gap variation on quality on MRI brain of T1WI spin echo axial pieces, seen from p value of SNR (0.010) and CNR (0.001) <0.05. In addition there is influence, there is also differences in anatomical image information on MRI brain pieces axial T1WI spin echo, seen from p value that is 0.001 <0.05. seen from the mean rank interslice gap 10% has the best anatomical image information. Conclusion : There is an effect of interslice gap on image quality on MRI brain axial of T1WI spin echo, there is difference of MRI brain anatomical image information of T1WI spin echo axial with interslice gap variation, interslice gap 10% value has the most optimal information.